TRI HITA KARANA BASED SOCIAL VALUE REPORTING MODEL FOR BALINESE MSMEs - Wiguna, I Gd Nandra Hary; Dewi, Nyoman Ayu Wulan Trisna (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to design a social value reporting model for micro, small, and medium enterprises (MSMEs) in Bali by integrating local wisdom specifically, the Tri Hita Karana philosophy into accounting practices. MSMEs in this region contribute not only economically but also play a significant role in preserving social and cultural values through practices such as ngayah (voluntary service). Unfortunately, these contributions are not adequately reflected in conventional financial reports. The research questions how social contributions rooted in local wisdom can be systematically incorporated into the financial reporting practices of MSMEs. The novelty of this research lies in proposing a Tri Hita Karana-based social reporting model, which has rarely been explored in MSME accounting literature. This study employs a qualitative case study approach involving traditional culinary MSMEs in Buleleng Regency. Data were collected through semi-structured interviews, field observations, and documentation studies. The data were analyzed thematically. Findings reveal that MSMEs make substantial social contributions, yet these are not formally documented. Consequently, the study proposes a prototype reporting model that categorizes contributions under three dimensions of Tri Hita Karana: Parahyangan, Pawongan, and Palemahan. The study concludes that incorporating local values into financial reporting enhances the relevance of accounting information and strengthens the cultural identity of MSMEs in Bali. This research offers both practical and theoretical contributions to the development of culturally grounded social accounting.